DESAIN LAPANGAN BASKET SMAN 70 JAKARTA - Maria Veronica Gandha; Nina Carina (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Tarumanagara, 2021)
To prepare for Face-to-face Learning in the Pandemic Period, SMA 70 is preparing for the best facilities and infrastructure. One of the facility needed is an open field. SMA 70 has a large outdoor area that can be used for outdoor activities both for sports and for other activities such as ceremonies and even outdoor classroom. Sport as one of the mandatory subject at school and is also the second bastion of COVID-19 prevention. The face-to-face learning activities that stop since March 2020 has caused some facilities and infrastructure poorly maintained. The 70th High School Basketball Court is an example of an infrastructure that has been damaged. The previous basketball court renovation transform the concrete platform to asphalt finishing which is far from certain requirements a basketball court should meet, such as size standards, safety, comfort and others. For this reason, renovation are needed to create a basketball court that is friendly and safe for students to use for their various activities. SMAN 70 as a public school has many limitations of facilities and infrastructure, such as in in funding, in knowledge and manpower. For this need, the team have a collaboration with SMA 70 conducted a program with the title